2021
DOI: 10.4236/ijohns.2021.104026
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Correlations of the Voice Category (VC) in Professional Singers with Oropharyngeal and Laryngeal Anatomy Using Stroboscopy and Cervical Posteroanterior Radiography

Abstract: Objective(s): The aim of this study is to explore if there is a correlation between the typical voice classification and the oropharyngeal and laryngeal morphology, using video laryngeal stroboscopy and cervical posterior-anterior radiography on professional singers in Greece. Methods: 55 professional singers (28 females: 7 sopranos, 12 mezzo-sopranos, and 9 contraltos; 27 males: 8 tenors, 12 baritones and 7 basses) were recruited for this study. All participants underwent stroboscopic and cervical posterior-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…groups of individuals share large-scale shape features. The existence of laryngeal morphotypes among humans has been hypothesized, mostly in the context of structural adaptations for specific voice categories (6, 47, 49, 50). The sources of such morphological variation were largely unknown but this study demonstrated a quantitative approach validate cluster identity.…”
Section: Discussionmentioning
confidence: 99%
“…groups of individuals share large-scale shape features. The existence of laryngeal morphotypes among humans has been hypothesized, mostly in the context of structural adaptations for specific voice categories (6, 47, 49, 50). The sources of such morphological variation were largely unknown but this study demonstrated a quantitative approach validate cluster identity.…”
Section: Discussionmentioning
confidence: 99%